2020
DOI: 10.1186/s12889-020-8275-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking cessation after atrial fibrillation diagnosis on the risk of cardiovascular disease: a cohort study of South Korean men

Abstract: Background: While smoking elevates the risk for cardiovascular disease (CVD) among atrial fibrillation (AF) patients, whether smoking cessation after AF diagnosis actually leads to reduced CVD risk is unclear. We aimed to determine the association of smoking cessation after AF diagnosis with subsequent CVD Risk among South Korean men. Methods: This retrospective cohort study included 2372 newly diagnosed AF male patients during 2003-2012 from the Korean National Health Insurance Service database. Self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…Previous studies have reported the impact of smoking status on cardiovascular outcomes in patients with AF [ 7 , 8 , 35 ]. One clinical cohort trial suggested that smoking may increase the risk of thromboembolic events in patients with anticoagulated AF by 2-fold [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported the impact of smoking status on cardiovascular outcomes in patients with AF [ 7 , 8 , 35 ]. One clinical cohort trial suggested that smoking may increase the risk of thromboembolic events in patients with anticoagulated AF by 2-fold [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Danish Diet, Cancer and Health cohort study, which included 3161 patients with incident AF, smoking did not show a significant increase in the risk of stroke in both men and women; however, this study did not include an analysis of the impact of quitting smoking after AF diagnosis [ 8 ]. Another recent study evaluated the association between smoking habits and the incidence of cardiovascular outcomes in patients with AF [ 35 ]. Although this study showed similar results to those of the current study, our study has several additional strengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) In South Korea, 41% of coronary artery diseases (CADs) and 26% of cerebrovascular disease are caused by tobacco, attributable to the high prevalence of smoking in adult Korean men. 7) 8) The smoking rate in adult Korean men declined rapidly from 79% in 1980 to 45% in 2007, but the rate of decline has slowed recently. 9) According to the 2018 National Health and Nutrition Survey report, the smoking rate in adult men was 36.7%.…”
Section: Trend In Risk Factors Of Cardiovascular Disease In Koreamentioning
confidence: 99%
“…The studies have reported that the aging process causes the progressive loss of physiological development at molecular, cellular and tissue levels which leads to an increase in CVDs [4]. On the other hand, several seminal researchers explored the link between CVDs and diabetes, which shows that CVDs are most prevalent cause of death in diabetic patients [5]- [7]. The level of the glucose gets high in diabetic patients which can damage the artery wall and increases deposition of fat in the coronary arteries, which might lead to possible heart arrest.…”
Section: Introductionmentioning
confidence: 99%